ANALYSIS OF INDONESIAN NATIONAL IDENTITY: POST CHANGES IN MANDATORY SCOUT EXTRACURRICULAR POLICY - Pratama Yoga Wica; Nurul Fajariah (SocioEdu: Sociological Education, 2025)
National identity is a characteristic of a country that must be taught to the next generation of the nation so that they understand it and are able to realize education that is oriented towards national education goals. Learning about national identity can be realized through extracurricular activities. One of the extracurricular activities in schools and colleges is scouting. This makes the role of extracurricular scouting education important. Initially, extracurricular scouting was a mandatory activity, but over time there was a government policy that changed extracurricular scouting to only be an option. So the purpose of this writing is to analyze changes in extracurricular scouting regulations for Indonesian national identity. The type of research is a qualitative approach with a literature review method that analyzes changes in extracurricular scouting regulations for Indonesian national identity education. The results of this study are that even though the regulations on extracurricular scouting activities have been changed, the material in scouting activities is still continuous with the material on the nation's national identity. There are still many differences of opinion regarding the changes to the scouting extracurricular activities, of course this is something that is worth discussing by the rule makers.